Implikasi prinsip kerjasama dalam film Ar-Risalah karya Mustopha Akkad berdasarkan prespektif Grice - Azhara, Aulia (Maliki Interdisciplinary Journal, 2024)
This research was raised with the aim of describing the forms of speech that exist in various theories of the application of the principle of cooperation in the film Ar-Risalah from Grice's perspective. The method used in this study is descriptive qualitative by explaining the application of the principle of cooperation namely, maxim of quality, maxim of quantity, maxim of relevance, and maxim of manner. Data collection techniques used are watching, listening, and note-taking techniques. The data sources generated from this research are primary data sources and secondary data sources. The primary data source was generated from the film "Ar-Risalah" by Musthopha Akkad. While secondary data sources are generated from the results of previous research, journals, articles, and several other supporting books. The data validation technique used in this study was by watching films repeatedly and discussing the same theme with colleagues. The results of this study are interesting to study because there are functions of the application of the principle of cooperation, namely, maxim of quality, maxim of quantity, maxim of relevance, and maxim of manner.